R&D-hindering collusion - Emanuele Bacchiega; Luca Lambertini; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
In an extended version of d'Aspremont and Jacquemin's (1988) R&D competition model we find a region where the game is a prisoner's dilemma: firms still invest in R&D but they would obtain a higher profit by not investing at all. In a repeated version of the game, we prove that firms implicitly tend to collude and refrain from investing in R&D, thus decreasing social welfare. When this happens, inviting firms to form a joint venture appears as a remedy to the lack of innovation efforts rather than the excess thereof.
Keywords: 330